Implementation of Learning Management for Children with Special Needs in Elementary Schools - Muhamad Suhardi; Mar'atus Sholihah (Universitas Pendidikan Ganesha, 2025)
Inclusive education plays an important role in ensuring that all children, including children with special needs, have equal rights in education. This study aims to evaluate the implementation of learning management for children with disabilities, focusing on the planning, implementation and evaluation stages of learning. The approach used was qualitative with descriptive methods, involving principals, teachers and educators as participants. Data were collected through in-depth interviews, observations and documentation studies, which were analyzed using the Miles and Huberman model. The results showed that learning planning for children with disabilities was systematically organized through initial assessment, flexible curriculum development and selection of appropriate learning methods. In the implementation stage, teachers apply strategies such as the multisensory approach, experiential learning and special assistance. Evaluation is conducted regularly through formative and summative assessments to measure the effectiveness of learning in students' academic, social and emotional aspects. Supporting factors in inclusive education include supportive policies, teacher competence, and parental and community involvement. However, there are barriers such as limited resources, lack of specialist educators and lack of supporting facilities. This study recommends increasing training for educators, providing more adequate facilities and strengthening cooperation between schools, government and communities to support optimal inclusive education. With the right strategies, learning for children with disabilities can be more effective and sustainable.